Effect of recreational activities in urban parks on the overall condition of sedentary older adults - Hakman, Anna; ANDRIEIEVA, OLENA; KASHUBA, VITALII; DUTCHAK, MYROSLAV; TOMENKO, OLEKSANDR; CHEREDNICHENKO, SERHIY; BOLSHAKOVA, IRINA (My University, 2021)
The objective of the study was to examine the effect of an outdoor program including health-enhancing and recreational physical activities in urban parks on physical and emotional status of the elderly. The following methods were used in the study: physical activity was assessed with Framingham Physical Activity Index, quality of life was studied with Medical Outcomes Study Questionnaire Short Form (SF-36), life satisfaction was evaluated with Life Satisfaction Index, cognitive functions were assessed with MMSE test, emotional status was assessed with Well-being-Activity-Mood (WAM) technique, test PWC150 was used to assess physical working capacity, and psychosocial adjustment was evaluated using the modified Rogers and Dymond’s questionnaire. The data were analyzed using statistics. The study involved 51 women and 50 men aged 60-65 years. The outdoor program was developed for old-age people and lasted 6 months. The program included three periods: preparatory (lasted one month), main (lasted four months) and maintaining (lasted one month). It includes the following physical activities: Nordic walking, breathing exercises and stretching, exercises at various park locations using stairs, benches, Swedish wall, horizontal bar, and parallel bars. The effectiveness of the outdoor program of health-enhancing and recreational physical activity in urban parks was evidenced by the positive changes in the emotional state (5.5-6.2 points), in the indicators of quality of life (physical activity was 81.3±0.6 points in men and 85.8±0.6 points in women, general health was 76.4±0.3 points in men and 75.4±0.3 points in women, social activity was 72.3±0.7 points in men and 78.5±0.9 points in women, viability was 72.6±1.1 points in men and 83.4±1.3 points in women, and mental health was 72.6±1.1 points in men and 76.4±0.7 points in women), in the life satisfaction index (25% of men and 27.4% of women had a high level of LSI), in physical fitness (42.0% of men and 25.5% of women had a higher than average level of physical working capacity), and in mental working capacity (13.7% of women and 18.0% of men had a very high level of concentration). Participation in the developed outdoor program contributed to increasing the levels of physical activity and mental and physical working capacity, improving quality of life and life satisfaction, psychosocial adjustment, cognitive functions, and emotional status (WAM) of the elderly. The results of the study were used to develop and substantiate the social project ‘Active parks are healthy locations in Ukraine’.
Keywords: old age, physical activity, general health condition, quality of life, satisfaction, outdoor program.